A brief review on thermal behaviour of PANI as additive in heat transfer fluid - Sofiah, A. G. N.; Samykano, M.; Shahabuddin, S.; Kadirgama, K.; Pandey, A. K.; Noor, M. M. (Penerbit UTHM, 2021)
Since a decade ago, investigation on nanofluids has grown significantly owing to its enhanced thermal properties compared to conventional heat transfer fluids. This engineered nanofluid has been widely used in the thermal engineering system to improve their energy consumption by improving the thermal efficiency of the system. The addition of nano-size particles as additives dispersed in the base fluids proved to significantly either improve or diminish the behaviour of the base fluids. The behaviour of the base fluid highly depends on the properties of the additives material, such as morphology, size, and volume fraction. Among the variety of nanoparticles studied, the conducting polymers have been subject of high interest due to its high environmental stability, good electrical conductivity, antimicrobial, anti-corrosion property and significantly cheap compared to other nanoparticles. As such, the main objective of the present review is to provide an overview of the work performed on thermal properties performance of conducting polymers based nanofluids.